Comparison of incisors changes in skeletal Class II and Class III malocclusions treated with conventional orthognathic surgery and surgery-first approach - Huilca, Gonzalo Paúl Velásquez (2024)
Objective: This study aimed to compare the changes of maxillary and mandibular incisors in skeletal Class II and Class III malocclusions patients treated with conventional orthognathic surgery (COS) and surgery-first approach (SFA). Material and methods: From the Class II malocclusion sample: COS group comprised 23 patients (10 males, 13 females) with a mean pretreatment age of 27.64 ± 8.61 years, treated during a mean period of 2.98 ± 1.33 years. SFA group comprised 23 patients (7 males, 16 females) with a mean pretreatment age of 30.33 ± 8.30 years, treated during a mean period of 1.61 ± 1.18 years. From the Class III malocclusion sample: COS group comprised 23 patients (13 males, 10 females) with a mean pretreatment age of 23.81 ± 8.15 years, treated during a mean period of 3.25 ± 1.29 years. SFA group comprised 23 patients (9 males, 14 females) with a mean pretreatment age of 25.53 ± 6.88 years, treated during a mean period of 1.34 ± 0.70 years. Lateral cephalometric radiographs were obtained at pretreatment (T1) and posttreatment (T2). Intergroup comparisons were performed with independent T-test. Results: From the Class II malocclusion sample: In the intergroup comparison between treatment changes, the FMA and LAFH decreased significantly more with the treatment in the COS group than in the SFA group. The mandibular incisors were significantly more intruded with treatment in the COS group than in SFA group. From the Class III malocclusion sample: In the intergroup comparison between treatment changes, the maxillary incisors were significantly more palatally inclinated in the SFA group than in the COS group. The interincisal angle was significantly reduced in the COS group and significantly increased in the SFA group. Conclusions: There was no difference in maxillary and mandibular incisor changes in skeletal Class II and Class III malocclusions patients treated with conventional orthognathic surgery and surgery-first approach.